To the power negative?

Algebra Level 2

If a = ( 3 + 2 ) 3 a=(\sqrt{3}+\sqrt{2})^{-3} and b = ( 3 2 ) 3 b=(\sqrt{3}-\sqrt{2})^{-3} , find the value of ( a + 1 ) 1 + ( b + 1 ) 1 (a+1)^{-1}+(b+1)^{-1} .


The answer is 1.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Sabhrant Sachan
May 11, 2016

Relevant wiki: Surds

We have to calculate : ( a + 1 ) 1 + ( b + 1 ) 1 1 a + 1 + 1 b + 1 a + b + 2 a b + a + b + 1 a b = ( 3 + 2 ) 3 × ( 3 2 ) 3 = 1 a + b + 2 a b + a + b + 1 = a + b + 2 a + b + 2 A n s = 1 \text{We have to calculate : }(a+1)^{-1}+(b+1)^{-1} \implies \dfrac{1}{a+1}+\dfrac{1}{b+1} \implies \dfrac{a+b+2}{ab+a+b+1} \\ ab=(\sqrt{3}+\sqrt{2})^{-3}\times(\sqrt{3}-\sqrt{2})^{-3}=1 \\ \implies\dfrac{a+b+2}{ab+a+b+1} = \dfrac{a+b+2}{a+b+2} \implies \boxed{Ans=1}

very goooood solution...+1

Ayush G Rai - 5 years, 1 month ago

Log in to reply

thank you ayush ...

Sabhrant Sachan - 5 years, 1 month ago

@Sabhrant Sachan How do you know that a b = ( 3 + 2 ) 3 × ( 3 2 ) 3 = 1 \displaystyle ab = ( \sqrt { 3 } + \sqrt { 2 } ) ^ { -3 } \times ( \sqrt { 3 } - \sqrt { 2 } ) ^ { -3 } = 1 ?

. . - 3 months ago

( 3 + 2 ) 3 × ( 3 2 ) 3 = ( 3 2 ) 3 = 1 (\sqrt{3}+\sqrt{2})^{-3}\times(\sqrt{3}-\sqrt{2})^{-3}= (3-2)^{-3} = 1

Sabhrant Sachan - 1 month, 3 weeks ago
Hung Woei Neoh
May 11, 2016

a = ( 3 + 2 ) 3 = 1 ( 3 + 2 ) 3 a + 1 = 1 ( 3 + 2 ) 3 + 1 = 1 + ( 3 + 2 ) 3 ( 3 + 2 ) 3 ( a + 1 ) 1 = ( 1 + ( 3 + 2 ) 3 ( 3 + 2 ) 3 ) 1 = ( 3 + 2 ) 3 1 + ( 3 + 2 ) 3 b = ( 3 2 ) 3 = 1 ( 3 2 ) 3 b + 1 = 1 ( 3 2 ) 3 + 1 = 1 + ( 3 2 ) 3 ( 3 2 ) 3 ( b + 1 ) 1 = ( 1 + ( 3 2 ) 3 ( 3 2 ) 3 ) 1 = ( 3 2 ) 3 1 + ( 3 2 ) 3 a=(\sqrt{3}+\sqrt{2})^{-3}=\dfrac{1}{(\sqrt{3}+\sqrt{2})^3}\\ a+1 = \dfrac{1}{(\sqrt{3}+\sqrt{2})^3}`+ 1 = \dfrac{1 + (\sqrt{3}+\sqrt{2})^3}{(\sqrt{3}+\sqrt{2})^3}\\ (a+1)^{-1} = \left(\dfrac{1 + (\sqrt{3}+\sqrt{2})^3}{(\sqrt{3}+\sqrt{2})^3}\right)^{-1} = \dfrac{(\sqrt{3}+\sqrt{2})^3}{1 + (\sqrt{3}+\sqrt{2})^3}\\ b=(\sqrt{3}-\sqrt{2})^{-3}=\dfrac{1}{(\sqrt{3}-\sqrt{2})^3}\\ b+1 = \dfrac{1}{(\sqrt{3}-\sqrt{2})^3}`+ 1 = \dfrac{1 + (\sqrt{3}-\sqrt{2})^3}{(\sqrt{3}-\sqrt{2})^3}\\ (b+1)^{-1} = \left(\dfrac{1 + (\sqrt{3}-\sqrt{2})^3}{(\sqrt{3}-\sqrt{2})^3}\right)^{-1} = \dfrac{(\sqrt{3}-\sqrt{2})^3}{1 + (\sqrt{3}-\sqrt{2})^3}

( a + 1 ) 1 + ( b + 1 ) 1 = ( 3 + 2 ) 3 1 + ( 3 + 2 ) 3 + ( 3 2 ) 3 1 + ( 3 2 ) 3 = ( 3 + 2 ) 3 ( 1 + ( 3 2 ) 3 ) + ( 3 2 ) 3 ( 1 + ( 3 + 2 ) 3 ) ( 1 + ( 3 2 ) 3 ) ( 1 + ( 3 + 2 ) 3 ) = ( 3 + 2 ) 3 + ( 3 2 ) 3 + 2 ( 3 + 2 ) 3 ( 3 2 ) 3 1 + ( 3 + 2 ) 3 + ( 3 2 ) 3 + ( 3 + 2 ) 3 ( 3 2 ) 3 = ( 3 + 2 ) 3 + ( 3 2 ) 3 + 2 ( ( 3 + 2 ) ( 3 2 ) ) 3 1 + ( 3 + 2 ) 3 + ( 3 2 ) 3 + ( ( 3 + 2 ) ( 3 2 ) ) 3 = ( 3 + 2 ) 3 + ( 3 2 ) 3 + 2 ( 3 2 ) 3 1 + ( 3 + 2 ) 3 + ( 3 2 ) 3 + ( 3 2 ) 3 = ( 3 + 2 ) 3 + ( 3 2 ) 3 + 2 ( 1 ) 3 1 + ( 3 + 2 ) 3 + ( 3 2 ) 3 + ( 1 ) 3 = ( 3 + 2 ) 3 + ( 3 2 ) 3 + 2 ( 3 + 2 ) 3 + ( 3 2 ) 3 + 2 = 1 (a+1)^{-1} + (b+1)^{-1}\\ =\dfrac{(\sqrt{3}+\sqrt{2})^3}{\color{#EC7300}{1 + (\sqrt{3}+\sqrt{2})^3}} + \dfrac{(\sqrt{3}-\sqrt{2})^3}{\color{#20A900}{1 + (\sqrt{3}-\sqrt{2})^3}}\\ =\dfrac{(\sqrt{3}+\sqrt{2})^3 \color{#20A900}{\left(1 + (\sqrt{3}-\sqrt{2})^3 \right)} +(\sqrt{3}-\sqrt{2})^3 \color{#EC7300}{\left(1 + (\sqrt{3}+\sqrt{2})^3 \right)}}{\color{#20A900}{\left(1 + (\sqrt{3}-\sqrt{2})^3 \right)} \color{#EC7300}{\left(1 + (\sqrt{3}+\sqrt{2})^3 \right)}}\\ =\dfrac{(\sqrt{3}+\sqrt{2})^3 + (\sqrt{3}-\sqrt{2})^3 +2\color{#D61F06}{(\sqrt{3}+\sqrt{2})^3 (\sqrt{3}-\sqrt{2})^3}}{1 +(\sqrt{3}+\sqrt{2})^3 + (\sqrt{3}-\sqrt{2})^3 +\color{#D61F06}{(\sqrt{3}+\sqrt{2})^3 (\sqrt{3}-\sqrt{2})^3}}\\ =\dfrac{(\sqrt{3}+\sqrt{2})^3 + (\sqrt{3}-\sqrt{2})^3 +2\color{#D61F06}{\left((\sqrt{3}+\sqrt{2})(\sqrt{3}-\sqrt{2})\right)^3}}{1 +(\sqrt{3}+\sqrt{2})^3 + (\sqrt{3}-\sqrt{2})^3 +\color{#D61F06}{\left((\sqrt{3}+\sqrt{2})(\sqrt{3}-\sqrt{2})\right)^3}}\\ =\dfrac{(\sqrt{3}+\sqrt{2})^3 + (\sqrt{3}-\sqrt{2})^3 +2\color{#D61F06}{\left(3-2\right)^3}}{1 +(\sqrt{3}+\sqrt{2})^3 + (\sqrt{3}-\sqrt{2})^3 +\color{#D61F06}{\left(3-2\right)^3}}\\ =\dfrac{(\sqrt{3}+\sqrt{2})^3 + (\sqrt{3}-\sqrt{2})^3 +2\left(1\right)^3}{1 +(\sqrt{3}+\sqrt{2})^3 + (\sqrt{3}-\sqrt{2})^3 +\left(1\right)^3}\\ =\dfrac{(\sqrt{3}+\sqrt{2})^3 + (\sqrt{3}-\sqrt{2})^3 +2}{(\sqrt{3}+\sqrt{2})^3 + (\sqrt{3}-\sqrt{2})^3 +2}\\ =\boxed{1}

very lengthy solution but good..+1

Ayush G Rai - 5 years, 1 month ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...